Efektivitas Program Bimbingan Karir Berbasis Teori Super untuk Mengembangkan Identitas Vokasional Remaja - Agungbudiprabowo Agungbudiprabowo; Nurhudaya Nurhudaya; Amin Budiamin (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
The study aims to test the effectiveness of career guidance program to develop vocational identity of students. The study uses a quantitative approach with quasi experimental methods and non-equivalent pretest-posttest control group design. The study was conducted in SMK Muhammadiyah Imogiri Yogyakarta by taking a research subject that is a class XI student who is determined by random cluster sampling technique. An instrument which is used is the scale of vocational identity and observation guidelines. Results showed empirically career guidance program interventions based theory of Super effective to develop vocational identity of students. This research can be a reference for school counselor in developing vocational identity of students in the school especially those who are in adolescence